HISTORY LEARNING ACTIVITY OF NAN OLD CITY AREA BY USING GROUP INVESTIGATION PROCESS AND GAMIFICATION FOR THIRD YEAR SECONDARY SCHOOL STUDENTS AT SRISAWATWITTAYAKARNCHANGWATNAN SCHOOL - Wartkunchorn, Nontaya; Pooncharoen, Nattachet (Journal of Buddhist Education and Research (JBER), 2023)
This research aims to develop historical learning activities in the old city of Nan by using the investigation process together with the game conception concept. For students in Mathayom 3, Srisawatwittayakarnchangwatnan School, Nan Province which is a qualitative research. The main informant groups are the learners, historical educators, and a group of teachers who has experience in teaching and learning management in schools, totaling 45 people, with the research area scopes, which are Nai Wiang Sub-district, Mueang Nan District and Muang Tut Sub-district, PhuPiang District, Nan Province. The data was analyzed, using inductive summaries by descriptive notes. and to check the reliability of the triangular pattern by data collection method. For students in Mathayom 3, Srisawatwittayakarnchangwatnan School, Nan Province. It is an activity to learn about the local history of Nan province which focuses on the learners to acquire skills from learning in the form of Active Learning by using the process of searching for knowledge consisting of 5 important steps which are interest -building or engagement, exploration and discovery, explanation, elaboration and evaluation. Throughout the course of the knowledge investigation, the researcher uses the concept of gamification such as name points, badges, and rankings, to stimulate learners’ enthusiasm in learning. The results of the research revealed that there are four important issues, namely, learners, teachers, media and learning resources, and learning activities. As a result, learners are awakened to the local history of Nan Province that is related to Thai history. This will make learners have the persistence of knowledge towards sustainable development as well as leading to the awareness of their local love